(3GdeUGMas - (3YHO Gddg Hf SdjeGf Hf GdCTYK GdCROj GdSLSJGfj, CHh HcQ Hf CHj OGhO,J (B316 (3g` s
(3ChdgG (B:s
(3GdBf MXjJ HGdRHOI hHQF GdOgQ EdgjG ef GdYgOg hCNP ai MOjK GdaQM s
(3BNQgG (B:s
(3jfJgi HHGH MQb GdeUMa EPG ESJZfi Yfg s
(3GdfSNI HgG MhGTs
(3HBNQg SeGYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B91 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B60s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs